Analisis Sosio-Ekologi Aktivitas Pertanian di Desa Bonthula Kabupaten Gorontalo - Eka Reza Saputra Widodo; Dewi Wahyuni K. Baderan; Fitryane Lihawa (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
This study analyzes the relationship between social and ecological aspects of agricultural activities in Bonthula Village, Gorontalo Regency. Most of the community relies on maize cultivation as the main commodity, but diversification into perennial crops such as nutmeg, durian, rambutan, cloves, coconut, cocoa, and avocado is also practiced tomaintain soil balance and increase income. The community's ecological awareness is reflected in their understanding of the benefits of perennial crops in improving soil fertility, maintaining moisture, and preventing degradation caused by monoculture maize. The village government supports these practices through perennial crop seed assistance programs aimed at promoting ecosystem sustainability and improving farmers' welfare. This research adopts a descriptive approach with data triangulation from interviews, observations, and document studies. The analysis reveals that the integration of perennial crop diversification and local policy support positively impacts the socio-economic and ecological aspects of Bonthula Village. This community-based agricultural management model can serve as a reference for implementing sustainable practices in other regions facing similar challenges.